Water‐Repellent Ionic Liquid Skinny Gels Customized for Aqueous Zn‐Ion Battery Anodes - Lee, Donggue; Kim, Hong‐I; Kim, Won‐Yeong; Cho, Seok‐Kyu; Baek, Kyungeun; Jeong, Kihun; Ahn, David B.; Park, Sodam; Kang, Seok Ju; Lee, Sang‐Young (Advanced functional materials, 2021)
Despite the enormous potential of aqueous zinc (Zn)‐ion batteries as a cost‐competitive and safer power source, their practical applications have been plagued by the chemical/electrochemical instability of Zn anodes with aqueous electrolytes. Here, ionic liquid (IL) skinny gels are reported as a new class of water‐repellent ion‐conducting protective layers customized for Zn anodes. The IL skinny gel (thickness ≈500 nm), consisting of hydrophobic IL solvent, Zn salts, and thiol‐ene polymer compliant skeleton, prevents the access of water molecules to Zn anodes while allowing Zn2+ conduction for redox reactions. The IL‐gel‐skinned Zn anode enables sustainable Zn plating/stripping cyclability under 90% depth of discharge (DODZn) without suffering from water‐triggered interfacial parasitic reactions. Driven by these advantageous effects, a Zn‐ion full cell (IL‐gel‐skinned Zn‐anode||aqueous‐electrolyte‐containing MnO2 cathode) exhibits high charge/discharge cycling performance (capacity retention ≈95.7% after 600 cycles) that lies beyond those achievable with conventional aqueous Zn‐ion battery technologies. Ionic liquid (IL) skinny gels are presented as a water‐repellent ion‐conducting protective layer customized for aqueous Zn‐ion battery anodes. The IL‐gel‐skinned Zn anode allows sustainable Zn plating/stripping behavior without water‐triggered interfacial parasitic reactions, thus enabling an aqueous Zn/MnO2 full cell to exhibit a high charge/discharge cycling performance (capacity retention ≈95.7% after 600 cycles).